China’s Gas Development Strategies (Advances in Oil and Gas Exploration & Production,, 2017)
This book is open access under a CC BY 4.0 license. This book examines how China can increase the share of natural gas in its energy system. China’s energy strategy has global ramifications and impact, and central to this strategy is the country’s transition from coal to gas. The book presents the culmination of a two-year collaboration between the Development Research Center of the State Council (DRC) and Shell.  With the Chinese government’s strategic aim to increase the share of gas in the energy mix from 5.8% in 2014 to 10% and 15% in 2020 and 2030 respectively, the book outlines how China can achieve its gas targets. Providing both quantifiable metrics and policy measures for the transition, it is a much needed addition to the literature on Chinese energy policy. The research and the resulting recommendations of this study have fed directly into the Chinese government’s 13th Five-Year Plan, and provide unique insights into the Chinese government and policy-making. Due to its global impact, the book is a valuable resource for policy makers in both China and the rest of the world.